A Well Infant With Coronavirus Disease 2019 With High Viral Load. (28th February 2020) - Kam, Kai-qian; Yung, Chee Fu; Cui, Lin; Tzer Pin Lin, Raymond; Mak, Tze Minn; Maiwald, Matthias; Li, Jiahui; Chong, Chia Yin; Nadua, Karen; Tan, Natalie Woon Hui; Thoon, Koh Cheng
Abstract: A well 6-month-old infant with coronavirus disease 2019 (COVID-19) had persistently positive nasopharyngeal swabs up to day 16 of admission. This case highlights the difficulties in establishing the true incidence of COVID-19, as asymptomatic individuals can excrete the virus. These patients may play important roles in human-to-human transmission in the community.